THE INFLUENCE OF WORK ENVIRONMENT AND COMPESATION ON EMPLOYEE PERFORMANCE IN THE NATIONAL DEFENSE AGENCY IN MAKASSAR CITY - Usmin, Annisa Zalshabila; Sahabuddin, Romansyah; Haeruddin, Muh. Ikhwan Maulana; Natsir, Uhud Darmawan; Burhanuddin (Journal Management & Economics Review (JUMPER), 2023)
This study aims to determine the effect of work environment and compensation on employee performance. This type of research is quantitative. The population of this study were all employees of the Makassar City National Land Agency (BPN) as many as 63 people. And the sample in this study is the entire population, namely 63 employees. Data collection techniques were carried out by distributing questionnaires directly to respondents at BPN Makassar City. The data analysis technique used is multiple linear regression analysis using Statistical Product Service Solution (SPSS). The results of this study indicate that there is a positive and significant influence between the Work Environment variable (X1) with a significance of 0.005 and Compensation (X2) with a significance of 0.000 on Employee Performance (Y).